ENT 530 Social Media Portfolio: Sugarholic Premium Cake_Syed Ahmad / Syed Ahmad Muhajir Syed Abdullah - Syed Abdullah, Syed Ahmad Muhajir (2021)
Sugarholic Premium Cake_Syed Ahmad is a new establish online business that is selling Sarawak Layer Cake. The types of Sarawak Layer Cake that Sugarholic Premium Cake_Syed Ahmad sells are “Belacan”, “Roboh” and “Lumut”. Sugarholic Premium Cake_Syed Ahmad are using high quality ingredient and imported butter for every cake that they are produce. A sweet buttery taste of Sarawak Layer Cake, and only a flavour for each cake making Sugarholic Premium Cake unique and standout from the others. The combinations make it taste full of each flavour and increase the meltiness in the mouth. The Sarawak Layer Cake by Sugarholic Premium Cake_Syed Ahmad comes with three variety of flavour which is Coco, Prune and Pandan, and two sizes which is loaf size and 7’inch square size. Sugarholic Premium Cake_Syed Ahmad products are suitable for everyone regardless of their age and gender as it does not contain any harmful ingredients. For now, the target market are the Sarawakian that reside in semenanjung, housewife and kids. Sugarholic Premium Cake_Syed Ahmad currently operates in Puncak Alam, Selangor and only through online. This due to Sugarholic Premium Cake is a home-based business. For now, Sugarholic Premium Cake_Syed Ahmad is promoting the products through Facebook. Sugarholic Premium Cake_Syed Ahmad is an online business owned and managed by Syed Ahmad Muhajir Bin Syed Abdullah. The recipe that i used in producing the Sarawak Layer Cake is from my grandmother and it can consider as the heritage recipe from 3 generations. Sugarholic Premium Cake_Syed Ahmad is a home-based business and provide delivery across all states in Malaysia including Sabah and Sarawak by using the courier service such as J&T Express, Grab, Lalamove and DHL eCommerce. In the future, Sugarholic Premium Cake_Syed Ahmad target to become the top demanding Sarawak Layer Cake product in Malaysia and make Sarawak Layer Cake well known worldwide.